Desordem em progresso: crime e criminalidade em Manaus (1905-1915) - (:unkn) unknown (Universidade Federal do Amazonas, 2014)
The main theme of this dissertation is the discussion of the relations between crime/criminality and the Police in Amazonas, during the early 20th century. Our goal is to comprehend the dynamics of the relationship between the Police and the citizens, discussing results obtained by the analysis of documents produced by the institution itself, as well as data provided by the period’s press and documents that reproduced the government’s official speeches, aiming to clarify how the different layers of the society were able to Interact in the urban environment, and how the police officer’s job was developed in the city’s routine, especially in the dealing with the population in general. We aim, therefore, to understand the elements related to the diversity of Manaus’s urban problems in the proposed period.
Keywords: Criminalidade - Manaus; Ambiente urbano - Manaus; CIÊNCIAS HUMANAS: HISTÓRIA